DOZ047.62: Fixed the gap, solved the problem? Children operated on of esophageal atresia: what happen 3 years later. (24th June 2019) - Bevilacqua, F; Ragni, B; Conforti, A; Morini, F; Dotta, A; Bagolan, P; Aite, L
Abstract: Background: With improvements in surgical care long-term morbidity of patients with esophageal atresia (EA) has been recently taken into account (Lees et al., 2018). Morbidities include gastrointestinal and respiratory complication, problems of nutrition and growth, feeding difficulties, oral aversion or food refusal (Menzies et al., 2016). Aim: Purpose of this study is to explore eating problems and its implications at 3 years in infants born with esophageal atresia. Methods: A retrospective study including all infants operated for EA at our Institution in the period ranging from January 2012 and January 2016 who attended our follow-up program. A specific interview was set up for the study. The interview was delivered by telephone by a trained psychologist. Results: Parents of 51 children (male = 67%) were interviewed. Twenty-two percent of children showed a growth <10th percentile; 30% presented oral aversion for a period of their life; 45% still have episodes of chock during meals and 18% of these had more than one episode a week; 45% suffer of GERD and 41% experienced recurrent respiratory problems; 37% of parents experience anxiety during meals. Fifty-seven percent attended kindergarten (8% with a dedicated educator during meal time), and 92% attended preschool (26% with dedicated educator during meal time). Currently 67% of the families benefit of social facilities. Conclusions: Three years after surgical repair of the structural defect, a high percentage of family still experience physical and psychological problems related to eating behavior of their children. Efforts of the health care team as well as research should focus on how to prevent eating problems and improve quality of life both of children and families.